EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) BERBASIS MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V - Nur Aliffia, Indri; Irwan Setyowidodo; Yunus Tanthowi (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This Classroom Action Research (CAR) aims to improve the mathematics learning outcomes of fifth-grade students at SDN Besuk 1 through the implementation of the Realistic Mathematics Education (RME) approach supported by concrete media. The study was motivated by students’ low academic performance in mathematics and their limited engagement during the learning process. The research adopted the Kemmis and McTaggart action research model, which was carried out in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects of the study were 25 fifth-grade students. Data were collected through classroom observation, student learning assessments, and documentation. The instruments used included observation sheets for learning activities and evaluation test items. The findings showed a significant improvement in students’ learning outcomes, with the percentage of students achieving the minimum learning criteria increasing from 40% in the pre-cycle to 60% in the first cycle, and reaching 88% in the second cycle. Moreover, there was a notable improvement in students’ learning activity, particularly in terms of participation, engagement, and conceptual understanding. The use of concrete media enabled students to grasp mathematical concepts more meaningfully and contextually. Therefore, it can be concluded that the RME approach combined with concrete media is effective in enhancing fifth-grade students’ mathematics learning outcomes.